Guideline for soil biology data collection in Ethiopia: National standard - Mnalku, Abere; Demissie, Negash; Assefa, Fassil; Tamene, Lulseged D. (Ethiopian Institute of Agricultural Research, 2020)
Recently, recognition has been growing of the power of data and information for better decisionmaking and service provision in agriculture. To ensure good data quality, an agreed standard to collect, store, and share data along the agricultural value chain is required. With this background, the purpose of this guideline is to provide guidance on standardizing soil biology data collection and thereby enhance temporal and spatial data interoperability. Standard field research design, data collection, and data reporting are required for well-informed meta-analyses and syntheses of agricultural research data as well as for making these data more accessible for calibration and evaluation of process-based models. Hence, this guideline is a contribution toward enabling meta-analysis of different data collected over years and/or space to accumulate evidence and generate new knowledge or insights to facilitate informed decision-making in the agricultural sector in general and in the crop development subsector. This guideline is compiled and intended for use by researchers, academicians, students, and other interested professionals in Ethiopia and beyond. The guideline is developed based on accepted standards and procedures in the field. Nevertheless, it is not exhaustive in its coverage of the soil biology data types and crops grown in the country. Hence, additions and updates depending on the development of research facilities, the ever-changing focus of agricultural research and production systems, and advances in technology are warranted.